POLA PEMBELAJARAN PENDIDIKAN ILMU PENGETAHUAN SOSIAL BERBASIS KEARIFAN LOKAL DI KELAS IV SEKOLAH DASAR NEGERI 0 BUANTAN BESAR KECAMATAN SIAK KABUPATEN SIAK - Eddy Noviana; Erlisnawati; Rifka Mahira Bakri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
Learning social science education gives a chance to give attention to caring for and using the surrounding area. The empirical fact in learning social science education before shows that the teacher is the only person who gives information, which is called teacher-centered learning. Learning materials used focus on textbooks, while the materials in the textbooks do not adopt or relate to local superiority and wisdom. This research focuses on the development of teaching materials for learning social science education in primary schools based on local wisdom, aligned with competency standards and basic standards in the first semester of grade IV. This research aims to develop teaching materials for learning social science education in primary schools based on local wisdom that can be used as a reference or supplement by teachers and students in learning. The method used is a research and development design. This research was conducted in four steps, namely: (1) literature study, (2) research planning, (3) research development, and (4) implementation. Data collection techniques used in this research include interviews, questionnaires, observations, documentation, and tests. Meanwhile, triangulation techniques and simple statistics were used to analyze the data. The results of the research show that (a) teaching materials for learning social science education based on local wisdom help teachers develop and relate learning materials in social science education to local potential, especially in Siak Regency, and (b) teaching materials for learning social science education based on local wisdom help students understand the potential and conditions of the surrounding area. This is proven by the increase in students’ understanding in learning social science education based on local wisdom, from an average pretest score of 31.73 to a posttest score of 53.85, with an average gain score of 0.33 in the fair category.